Youth Entrepreneurship for the Advancement of Entrepreneurial Potential - Agirr Laipuut Lopitf (Akademi Sertifikasi Profesi Internasional, 2023)
Programs developed or established by high school education levels to cultivate young entrepreneurs that comprehend entrepreneurship and possess the character and mindset of an entrepreneur. Moreover, the issue stemming from the establishment of this program is the deficiency of qualified educators who comprehend and can effectively implement entrepreneurship education. This issue presents universities with opportunities to actively contribute to the development of the younger generation's entrepreneurial character and mindset while also fostering a comprehensive and authentic understanding of entrepreneurship through community service. This training and mentorship will occur 14 times over the 7-month learning period. Two training sessions will be conducted at the conclusion of each week every month. This service will provide students with new insights for generating company ideas, considering multiple dimensions, including local wisdom, marketing, and customer perspectives. Furthermore, we have equipped students with the expertise to administer market analysis questionnaires, with the goal of understanding customer behavior in relation to their business concepts